Ubiquitous computing in sports: A review and analysis - Baca, A.; Dabnichki, P.; Heller, M.; Kornfeind, P. (Journal of Sports Sciences, 2009)
Ubiquitous (pervasive) computing is a term for a synergetic use of sensing, communication and computing. Pervasive use of computing has seen a rapid increase in the current decade. This development has propagated in applied sport science and everyday life.